Baseline interferon signaling in monocytes and antibody-mediated innate activation are associated with reactogenicity to mRNA vaccines - Natacha Madelon; Gustavo A. Ruiz Buendía; Paula Torres Rodriguez; Yves R. Donati; Paola Fontannaz; Matias Ciancaglini; Wafae Adouan; Emma Arsac; Nicolas Fonta; Rachel Goldstein; Nelli Heikkila; Nicolas Page; et al. (Science Translational Medicine, 2026)
The local and systemic symptoms that follow vaccination, collectively referred to as reactogenicity, are common, yet the mechanisms underlying individual variability remain poorly understood. Through longitudinal immune profiling of vaccinated individuals and mechanistic studies in mice, we identified key immunological determinants of reactogenicity induced by mRNA vaccines. Systemic adverse events were associated with stronger interferon and pro-inflammatory responses after the second dose of a COVID-19 mRNA vaccine, which were also correlated with the magnitude of the antigen-specific adaptive responses. This heightened inflammation occurred within 24 hours of vaccination, originated primarily from the injection site, and was characterized by enhanced recruitment and activation of myeloid cells, particularly monocytes. Two mechanisms contributed to this response: early interferon production by muscle T cells generated after the first dose and Fcγ receptor–dependent chemokine induction by vaccine antigen–specific antibodies. Consistently, serum antibody levels before vaccination correlated positively with reactogenicity. In addition to this local amplification mechanism, variability in reactogenicity was influenced by the baseline immune state, given that individuals with a preexisting interferon-stimulated gene signature in monocytes, detectable at both transcriptomic and epigenetic levels, were more prone to systemic symptoms. Together, our findings revealed molecular and cellular mechanisms driving vaccine reactogenicity, providing a framework for the design of less reactogenic vaccines.